Where Do Shareholder Gains in Hedge Fund Activism Come From? Evidence From Employee Pension Plans. (5th September 2022) - Agrawal, Anup; Lim, Yuree
Abstract: We find that defined benefit employee pension plans of firms that are targets of hedge fund activism experience underfunding and their defined contribution plans experience reductions in employer contributions. Pension underfunding occurs due to reduced employer contributions to the plans, which target firms justify by increasing the assumed rates of returns on plan investments and the discount rate used to compute the present value of plan obligations. Despite tilting plan investments toward riskier assets, pension fund performance does not improve after activists target a firm. Our evidence suggests that shareholder wealth gains from activism are partly wealth transfers from employees.